MINERALOGY OF THE VORONTSOVSKOE GOLD DEPOSIT (NORTHERN URALS). PART 2: NATIVE ELEMENTS, SULFIDES, ARSENIDES, TELLURIDES - A.V. Kasatkin; S.Yu. Stepanov; M.V. Tsyganko; R. Škoda; F. Nestola; J. Plášil; E. Makovicky; A.A. Agakhanov; R.S. Palamarchuk (Минералогия)
The paper continues a series of publications devoted to the mineralogy of the Vorontsovskoe gold deposit in the Northern Urals (Kasatkin et al., 2020). The paper reports on native elements, sulfides, arsenides and tellurides discovered at the deposit, their chemical compositions, as well as unit-cell parameters and optical properties of some minerals. Getchellite, duranusite, pararealgar and picotpaulite are found for the first time in Russia.